Self-compacting machine-made sand concrete for Yellow River flood plain climate and preparation method thereof
By using self-finishing machine sand formula and hydrophobic microcapsule technology in concrete in the yellow plain area, the crack problem caused by rapid evaporation of moisture is solved, and the crack resistance and durability of concrete are significantly improved.
Patent Information
- Application Number
- CN202411299974.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-04-01
AI Technical Summary
In the climate conditions of strong winds, dryness and temperature differences, the rapid evaporation of moisture leads to plastic shrinkage, dryness shrinkage and cracks, which seriously threatens the integrity and durability of concrete.
The self-finished machine sand concrete formula is adopted, and the water-repellent porous ceratops-acetylated di-starch phosphate-polydopamine microcapsules are introduced to enhance crack resistance and overall strength, and the moisture evaporation rate is reduced through the moisture management mechanism of the microcapsules.
It significantly improves the crack resistance and durability of concrete, reduces the formation of plastic shrinkage and dry shrinkage cracks, enhances the self-concentration and waterproofing properties of concrete, extends the service life of the structure and reduces maintenance costs.
Smart Images

Figure BDA0005047340440000101 
Figure BDA0005047340440000121 
Figure BDA0005047340440000131
Abstract
Description
Technical Field
[0001] The present application relates to the field of concrete technology, and in particular to a self-compacting machine-made sand concrete for the Yellow River flood plain climate and a preparation method thereof. Background Art
[0002] The Yellow River Flood Plain, located in western and northwestern Shandong, was formed by the alluvial deposits of the Yellow River. Its semi-humid warm temperate continental monsoon climate is characterized by strong winds, little precipitation, dry air and strong solar radiation, which causes the moisture in the fresh concrete in the area to evaporate rapidly, triggering plastic and drying shrinkage, and then producing plastic cracks and shrinkage cracks, which pose a major threat to the integrity and durability of concrete structures. Summary of the invention
[0003] In order to solve at least one of the above technical problems and develop a concrete with better durability, the present application provides a self-compacting machine-made sand concrete for the Yellow River flood plain climate and a preparation method thereof.
[0004] In a first aspect, the present application provides a self-compacting machine-made sand concrete for the Yellow River flood plain climate, wherein the concrete comprises the following raw materials in parts by weight: 400-450 parts of cement; Silica fume 85-105 parts; Mineral powder 200-220 parts; Fly ash 170-195 parts; Stone 900--1050 pieces 850-940 parts of machine-made sand; Steel fiber 283-295 parts; Polypropylene fiber 100-200 parts; Water reducing agent 18.5-21.5 parts; Hydroxyethyl cellulose 0.4-0.6 parts; Defoaming agent 0.5-1 part; 1319 parts of stimulant; 130-140 parts of water; Silane coupling agent KH-7925 - 10 parts; Hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules 100-200 points; The preparation method of the hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules comprises the following steps: A1. Add a (6-10) mol / L hydrochloric acid solution to the porous ceramsite, heat and stir for 3-5 hours in a water bath, centrifuge to separate the solid matter, and wash and grind the solid matter to obtain the porous ceramsite etched with hydrochloric acid; A2, the porous ceramsite etched with hydrochloric acid obtained in step A1, acetylated distarch phosphate and water are mixed, and ultrasonically dispersed for 50-70 minutes under ice bath conditions to obtain a suspension, and the obtained suspension is vacuum dried. When the vacuum degree in the dryer reaches -0.1 MPa during vacuum drying, it is maintained for 20-30 minutes, and then restored to 0.1 MPa; A3. After vacuum drying, centrifuge to separate the solid phase, wash the solid phase, vacuum dry for 24-30 hours, grind into powder, and obtain porous ceramsite loaded with acetylated distarch phosphate after hydrochloric acid etching; A4, tris(hydroxymethyl)aminomethane, dopamine hydrochloride, the porous ceramsite loaded with acetylated distarch phosphate obtained after hydrochloric acid etching in step A3, and water in a weight ratio of (2-3):(1-1.5):1:(180-200), and adjusting the pH to 8.0-9.0, ultrasonically dispersing for 15-20 minutes, stirring for 6-8 hours, centrifugally washing, and drying to obtain a porous ceramsite-acetylated distarch phosphate-polydopamine composite; A5, placing the porous ceramsite-acetylated distarch phosphate-polydopamine complex obtained in step A4 into a solution of hexadecyltrimethoxysilane and ethanol, soaking for 3-5 hours, and drying to obtain the hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules; The weight ratio of the porous ceramsite to the hydrochloric acid solution in step A1 is (10-12): (100-120); The weight ratio of the acetylated distarch phosphate and water in step A2 to the porous ceramsite in step A1 is (15-20): (60-80): 1; The weight ratio of hexadecyltrimethoxysilane, ethanol and the composite of porous ceramsite-acetylated distarch phosphate-polydopamine in step A4 is (0.8-1.2):20:10.
[0005] By adopting the above technical solution, a self-compacting machine-made sand concrete is designed to address the unique climatic conditions of the Yellow River Flood Plain, namely, strong winds, dryness, and large temperature differences, which lead to rapid loss of moisture in fresh concrete and the resulting plastic shrinkage, drying shrinkage, and cracks. This concrete formula carefully adjusts the proportions of various raw materials and innovatively introduces hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules, effectively solving the following technical problems: By optimizing the mix ratio, especially adding a high proportion of mineral admixtures such as silica fume, mineral powder, and fly ash, as well as an appropriate amount of steel fiber and polypropylene fiber, the crack resistance and overall strength of the concrete are significantly enhanced, and the resistance to environmental erosion is improved. The introduction of hydrophobic microcapsules provides additional fine closed cavities for concrete, which can effectively lock in moisture at the microscopic level, reduce the rate of moisture evaporation, and have a significant effect on combating shrinkage cracks. The effect of hydrophobic microcapsules in combating shrinkage cracks is mainly achieved through the following mechanisms: hydrophilic substances such as acetylated distarch phosphate are encapsulated inside the hydrophobic microcapsules, which can form tiny water storage spaces inside the concrete. When the water evaporates during the hardening process of concrete, these microcapsules can slowly release the internal water and replenish it into the capillary structure of the concrete, thereby delaying the evaporation rate of the water on the surface of the concrete and reducing the plastic shrinkage and shrinkage cracks caused by rapid drying. During the drying process of concrete, the uneven distribution of internal water will cause tensile stress inside. The existence of hydrophobic microcapsules is like a miniature stress buffer. With the migration of water and the change of environmental humidity, they can expand or shrink adaptively, which helps to evenly distribute internal stress and reduce local stress concentration, thereby avoiding or reducing the formation of cracks. The uniform distribution of microcapsules in concrete can improve the microstructure of concrete, reduce the number of large pores, and increase the proportion of small closed pores, which is conducive to improving the density of concrete and reducing the path of water transmission, further reducing the risk of shrinkage cracking. The hydrophobic modification of the microcapsule surface, such as treatment with hexadecyltrimethoxysilane, can improve the adhesion between the microcapsule and the concrete matrix, ensure that the microcapsule is stably distributed in the concrete and will not easily precipitate, so as to play its moisturizing and stress regulation functions more persistently. Through the combined effect of these mechanisms, hydrophobic microcapsules become an effective anti-cracking technical means, especially suitable for areas with extremely dry and windy and sandy climate conditions such as the Yellow River Flood Plain, which significantly improves the crack resistance and durability of concrete structures. The use of water reducers and hydroxyethyl cellulose not only reduces the water consumption of concrete and improves the water-cement ratio, but also ensures good fluidity and filling properties of concrete, so that concrete can be self-compacted under vibration-free or low-vibration conditions, reduce voids, and further improve the volume stability and durability of concrete. The addition of silane coupling agents improves the interfacial bonding between the components in concrete. At the same time, the hydrophobic modification of the microcapsule surface enhances the waterproof performance of concrete, which is particularly important for resisting seasonal wind and sand and saline-alkali erosion.In summary, the technical solution provided by this application, on the one hand, significantly improves the durability and crack resistance of concrete under the adverse climatic conditions of the Yellow River Flood Plain. The special microcapsule technology effectively inhibits the rapid loss of water and reduces the formation of plastic shrinkage and shrinkage cracks. On the other hand, the self-compactness of concrete is improved, ensuring the construction quality and the overall stability of the structure. At the same time, the interface performance and waterproofness of concrete are enhanced, the service life of the structure is extended, and the maintenance cost is reduced.
[0006] Optionally, the weight ratio of the polypropylene fiber to the hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules is 1:(0.8-1.2).
[0007] By adopting the above technical solutions, polypropylene fiber, as a traditional concrete reinforcement material, can effectively hinder the expansion of microcracks inside concrete and improve the crack resistance and toughness of concrete. The hydrophobic microcapsules used in conjunction with it, through their unique structure and composition, can not only provide an internal moisture management mechanism, but also form a physical barrier at the microcracks. The combination of the two forms a double protection for concrete cracks and significantly improves the overall crack resistance of concrete. The good adhesion between polypropylene fiber and concrete matrix, coupled with the uniform distribution of microcapsules in the concrete matrix, jointly enhances the bonding strength between the various phases inside the concrete, which is particularly critical for improving the overall stability of concrete and preventing the development of cracks. In summary, through the carefully designed ratio of polypropylene fiber to hydrophobic microcapsules, not only the physical and mechanical properties of concrete are enhanced, but also the shrinkage cracking problem under the special climatic conditions of the Yellow River Flood Plain is effectively combated through multiple mechanisms, providing a more reliable and efficient solution for concrete structures in this area. After the above hydrophobic microcapsules are broken in concrete, they can bring the following positive effects, especially for the protection and performance improvement of concrete under the special climatic conditions of the Yellow River Flood Plain: In the designed self-compacting machine-made sand concrete, the microcapsules play the role of intelligent moisture management. Specifically, when these specially designed hydrophobic microcapsules are broken due to changes in internal and external conditions (such as mechanical forces or the formation of microcracks inside the concrete) during the hardening and drying process of concrete, the hydrophilic materials such as acetylated distarch phosphate encapsulated inside them will gradually be released into the microenvironment of the concrete. As a hydrophilic substance, acetylated distarch phosphate can attract and retain a certain amount of water. During the drying stage of concrete, when the surrounding environment absorbs moisture from the concrete and causes the internal humidity to drop, these released hydrophilic components can slowly release the captured moisture and replenish the lost moisture to the capillary structure inside the concrete. This process effectively slows down the rapid loss of moisture inside the concrete, thereby alleviating the strong drying stress caused by rapid drying. As one of the contents of the microcapsules, polydopamine has good adhesion and certain catalytic activity. It can form a viscous medium at microcracks and promote the self-healing process of cracks. When fine cracks appear inside the concrete, the released substances can fill these cracks, react with the surrounding concrete or physically close the cracks, and improve the self-healing ability of the concrete. The rupture products of the microcapsules can fill the micropores in the concrete, optimize the microstructure of the concrete, improve the density and uniformity of the concrete, and thus enhance the overall performance of the concrete, including strength, impermeability and corrosion resistance. After the hydrophobic modified layer on the surface of the microcapsule is ruptured, its residue can be evenly distributed on the surface of the pores and cracks of the concrete, forming a hydrophobic barrier, which effectively prevents external moisture from penetrating into the interior of the concrete, reduces expansion and cracking caused by moisture intrusion, and improves the waterproof performance and durability of the concrete.The discontinuity of the distribution of microcapsules in concrete can serve as a tiny buffer zone for stress concentration points, which helps to disperse the stress inside the concrete, reduce local stress concentration, and further reduce the formation of cracks. In summary, the rupture and release of hydrophobic microcapsules in concrete is an active and intelligent strategy. Through dynamic regulation, self-healing promotion, structural optimization and other mechanisms, it effectively combats the degradation of concrete performance caused by climatic factors such as dryness and large temperature differences in the Yellow River Flood Plain, and significantly improves the durability and service life of concrete structures. Drying stress is one of the main causes of shrinkage cracks in concrete. When the water in concrete evaporates rapidly, the volume shrinks. If this shrinkage is constrained (for example, due to the hardness of the concrete itself or external constraints), tensile stress will be generated inside the concrete, which may eventually cause cracks on the surface or inside. The microcapsule technology maintains a relatively stable humidity level inside the concrete through this dynamic moisture regulation mechanism, reduces drying stress, significantly reduces the risk of shrinkage cracks, and improves the overall stability and durability of the concrete structure.
[0008] Optionally, the weight ratio of the polypropylene fiber to the hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules is 1:1.
[0009] Optionally, the total weight of the polypropylene fiber and the hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules accounts for 8-11% of the total weight of the self-compacting machine-made sand concrete for the Yellow River flood plain climate.
[0010] Optionally, the total weight of the polypropylene fiber and the hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules accounts for 10.5% of the total weight of the self-compacting machine-made sand concrete for the Yellow River flood plain climate.
[0011] Optionally, the water reducer is selected from polycarboxylate water reducer.
[0012] Optionally, the activator is selected from sodium sulfate.
[0013] Optionally, the stone has a particle size of 5-10 mm.
[0014] Optionally, the polypropylene fiber has a diameter of 30-50 μm and a length of 10-15 cm.
[0015] In a second aspect, the present application provides a method for preparing self-compacting machine-made sand concrete for the Yellow River flood plain climate, the preparation method comprising the following steps: S1, dissolving silane coupling agent KH-792 in ethanol, adding polypropylene fiber and steel fiber for impregnation treatment, and drying to obtain modified fiber; S2, dividing the water into two equal parts, mixing one part of the water with cement, mineral powder, fly ash, activator, silica fume, machine-made sand, gravel, and modified fiber to prepare a first mixed material; S3, adding hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules to the mixture and mixing and stirring to obtain a second mixture; S4, dissolving hydroxyethyl cellulose in the remaining water, adding the mixture to the second mixture and mixing, then adding a water reducer and a defoamer and mixing, and curing after forming to obtain the self-compacting machine-made sand concrete for the Yellow River flood plain climate.
[0016] By adopting the above technical scheme, the preparation method not only ensures the high performance of concrete through a carefully designed sequence of steps and material processing technology, but also specifically targets the special climatic conditions of the Yellow River Flood Plain, effectively solving the problems of rapid evaporation of water and crack formation, improving the durability and construction efficiency of concrete, and providing advanced concrete technology solutions for infrastructure construction in the Yellow River Flood Plain.
[0017] In summary, the present invention includes at least one of the following beneficial technical effects: 1. The technical solution provided by this application, on the one hand, significantly improves the durability and crack resistance of concrete under the adverse climatic conditions of the Yellow River Flood Plain. The special microcapsule technology effectively inhibits the rapid loss of water and reduces the formation of plastic shrinkage and shrinkage cracks. On the other hand, it improves the self-compactness of concrete, ensures the construction quality and the overall stability of the structure. At the same time, it enhances the interface performance and waterproofness of concrete, prolongs the service life of the structure, and reduces maintenance costs.
[0018] 2. Polypropylene fiber, as a traditional concrete reinforcement material, can effectively hinder the expansion of microcracks inside concrete and improve the crack resistance and toughness of concrete. The hydrophobic microcapsules used in conjunction with it, through their unique structure and composition, can not only provide an internal moisture management mechanism, but also form a physical barrier at the microcracks. The combination of the two forms a double protection against concrete cracks, significantly improving the overall crack resistance of concrete. The rupture and release of hydrophobic microcapsules in concrete is an active and intelligent strategy. Through dynamic adjustment, self-healing promotion, structural optimization and other mechanisms, it effectively combats the problem of concrete performance degradation caused by climatic factors such as dryness and large temperature differences in the Yellow River Flood Plain, and significantly improves the durability and service life of concrete structures.
[0019] 3. This preparation method, through a carefully designed sequence of steps and material processing technology, not only ensures the high performance of the concrete, but also specifically targets the special climatic conditions of the Yellow River Flood Plain, effectively solving the problems of rapid evaporation of water and crack formation, improving the durability and construction efficiency of the concrete, and providing advanced concrete technology solutions for infrastructure construction in the Yellow River Flood Plain. DETAILED DESCRIPTION
[0020] The present application is further described in detail below with reference to the embodiments.
[0021] Cement: Xianxian Yakai Instrument Sales Center, item number 1986.
[0022] Silica fume: CAS No. 1327-39-5, purity 99%.
[0023] Mineral powder: Lingshou County Chengming Mineral Products Processing Plant, content 98%.
[0024] Fly ash: Hebei Huishun Mining Co., Ltd., purity 99.
[0025] Gravel: The particle size of the gravel is 5-10mm.
[0026] Artificial sand: Lingshou County Yongzhuo New Material Technology Co., Ltd., particle size 2μm.
[0027] Steel fiber: Chengdu Keliang Building Materials Co., Ltd.
[0028] Polypropylene fiber: The diameter of polypropylene fiber is 30-50μm, the length is 10-15cm, and the purity is 95%.
[0029] Polycarboxylate water reducer: Jinan Boci Trading Co., Ltd., water reduction rate 40%, Hydroxyethyl cellulose: Guangdong Mingtong Biotechnology Co., Ltd., 9004-62-0.
[0030] Silicone defoamer: Shandong Sanju Chemical Technology Co., Ltd., content 99%.
[0031] Sodium sulfate: industrial grade sodium sulfate.
[0032] Silane coupling agent KH-792: content 99%.
[0033] Porous expanded clay: Henan Yuyan Environmental Protection Technology Co., Ltd., specification 3mm.
[0034] Acetylated distarch phosphate: CAS No. 68130-14-3, purity 98%.
[0035] Dopamine hydrochloride: CAS No. 62-31-7, purity 99%. Specific embodiments
[0036] Preparation Example 1 The present invention provides a hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsule, and the preparation method comprises the following steps: A1. Add a 6 mol / L hydrochloric acid solution to the porous ceramsite, heat and stir for 3 h in a water bath (80° C.), centrifuge to separate the solid matter, and wash and grind the solid matter to obtain the porous ceramsite etched with hydrochloric acid; A2, the porous ceramsite etched with hydrochloric acid obtained in step A1, acetylated distarch phosphate and water are mixed, and ultrasonically dispersed for 50 minutes under ice bath conditions to obtain a suspension, and the obtained suspension is vacuum dried. When the vacuum degree in the dryer reaches -0.1 MPa during vacuum drying, it is maintained for 20 minutes and then restored to 0.1 MPa; A3. After vacuum drying, centrifuge to separate the solid phase, wash the solid phase, vacuum dry for 24 hours, grind into powder, and obtain porous ceramsite loaded with acetylated distarch phosphate after hydrochloric acid etching; A4, tris(hydroxymethyl)aminomethane, dopamine hydrochloride, the porous ceramsite loaded with acetylated distarch phosphate after hydrochloric acid etching obtained in step A3, and water in a weight ratio of 2:1:1:180, and adjusting the pH to 8.0, ultrasonically dispersing for 15 minutes, stirring for 6 hours, centrifugally washing, and drying to obtain a porous ceramsite-acetylated distarch phosphate-polydopamine composite; A5, placing the porous ceramsite-acetylated distarch phosphate-polydopamine complex obtained in step A4 into a solution of hexadecyltrimethoxysilane and ethanol, soaking for 3 hours, and drying to obtain hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules; The weight ratio of the porous ceramsite to the hydrochloric acid solution in step A1 is 10:100; The weight ratio of acetylated distarch phosphate and water in step A2 to the porous ceramsite in step A1 is 15:60:1; the weight ratio of hexadecyltrimethoxysilane, ethanol and the composite of porous ceramsite-acetylated distarch phosphate-polydopamine in step A5 is 0.8:20:10.
[0037] Preparation Example 2 The difference between this preparation example and preparation example 1 is that the preparation method comprises the following steps: A1. Add 8 mol / L hydrochloric acid solution to the porous ceramsite, heat and stir for 4 h in a water bath (80° C.), centrifuge to separate the solid matter, and wash and grind the solid matter to obtain the porous ceramsite etched with hydrochloric acid; A2, the porous ceramsite etched with hydrochloric acid obtained in step A1, acetylated distarch phosphate and water are mixed, and ultrasonically dispersed for 60 minutes under ice bath conditions to obtain a suspension, and the obtained suspension is vacuum dried. When the vacuum degree in the dryer reaches -0.1 MPa during vacuum drying, it is maintained for 25 minutes and then restored to 0.1 MPa; A3. After vacuum drying, centrifuge to separate the solid phase, wash the solid phase, vacuum dry for 28 hours, grind into powder, and obtain porous ceramsite loaded with acetylated distarch phosphate after hydrochloric acid etching; A4, tris(hydroxymethyl)aminomethane, dopamine hydrochloride, the porous ceramsite loaded with acetylated distarch phosphate after hydrochloric acid etching obtained in step A3, and water are mixed in a loading ratio of 2.5:1.3:1:190, and the pH is adjusted to 8.0, ultrasonically dispersed for 18 minutes, stirred for 7 hours, centrifuged and washed, and dried to obtain a porous ceramsite-acetylated distarch phosphate-polydopamine complex; A5, the porous ceramsite-acetylated distarch phosphate-polydopamine complex obtained in step A4 is placed in a solution of hexadecyltrimethoxysilane and ethanol, soaked for 4 hours, and dried to obtain hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules; The weight ratio of the porous ceramsite to the hydrochloric acid solution in step A1 is 11:115; The weight ratio of acetylated distarch phosphate and water in step A2 to the porous ceramsite in step A1 is 18:75:1; the weight ratio of hexadecyltrimethoxysilane, ethanol and the composite of porous ceramsite-acetylated distarch phosphate-polydopamine in step A4 is 1:20:10.
[0038] Preparation Example 3 The difference between this preparation example and preparation example 1 is that the preparation method comprises the following steps: A1. Add a 10 mol / L hydrochloric acid solution to the porous ceramsite, heat and stir for 5 h in a water bath (80° C.), centrifuge to separate the solid matter, and wash and grind the solid matter to obtain the porous ceramsite etched with hydrochloric acid; A2, mixing the porous ceramsite etched with hydrochloric acid obtained in step A1, acetylated distarch phosphate and water, and ultrasonically dispersing for 70 minutes under ice bath conditions to obtain a suspension, vacuum drying the obtained suspension, and maintaining the vacuum degree in the dryer when it reaches -0.1 MPa for 30 minutes, and then returning to 0.1 MPa; A3. After vacuum drying, centrifuge to separate the solid phase, wash the solid phase, vacuum dry for 30 hours, grind into powder, and obtain porous ceramsite loaded with acetylated distarch phosphate after hydrochloric acid etching; A4, tris(hydroxymethyl)aminomethane, dopamine hydrochloride, the porous ceramsite loaded with acetylated distarch phosphate after hydrochloric acid etching obtained in step A3, and water are mixed at a loading ratio of 3:1.5:1:200, and the pH is adjusted to 9.0, ultrasonically divided for 20 minutes, stirred for 8 hours, centrifuged and washed, and dried to obtain a porous ceramsite-acetylated distarch phosphate-polydopamine composite; A5, placing the porous ceramsite-acetylated distarch phosphate-polydopamine complex obtained in step A4 into a solution of hexadecyltrimethoxysilane and ethanol, soaking for 5 hours, and drying to obtain hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules; The weight ratio of the porous ceramsite to the hydrochloric acid solution in step A1 is 12:120; The weight ratio of the acetylated distarch phosphate and water in step A2 to the porous ceramsite in step A1 is 20:80:1; the weight ratio of hexadecyltrimethoxysilane, ethanol and the porous ceramsite-acetylated distarch phosphate-polydopamine complex in step A4 is 1.2:20:10.
[0039] Example 1 The present embodiment provides a self-compacting machine-made sand concrete for the Yellow River flood plain climate, and the concrete includes the following raw materials by weight: 400 parts of cement; 85 parts of silica fume; 200 parts of mineral powder; 170 parts of fly ash; 900 parts of gravel; 850 parts of machine-made sand; 283 parts of steel fiber; 160 parts of polypropylene fiber; 18.5 parts of water reducer; 0.4 parts of hydroxyethyl cellulose; 0.5 parts of defoamer; 13 parts of activator; 130 parts of water; 25 parts of silane coupling agent KH-79; 160 parts of hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules; The hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules in this example are prepared by Preparation Example 1.
[0040] The method for preparing the self-compacting machine-made sand concrete for the Yellow River flood plain climate in this embodiment comprises the following steps: S1, dissolving silane coupling agent KH-792 in ethanol (the amount of ethanol is 10 times that of silane coupling agent KH-792), adding polypropylene fiber and steel fiber for impregnation treatment, and drying to obtain modified fiber; S2, dividing the water into two equal parts, mixing one part of the water with cement, mineral powder, fly ash, activator, silica fume, machine-made sand, gravel, and modified fiber to prepare a first mixed material; S2, adding hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules to the mixture and mixing and stirring to obtain a second mixture; S4. Dissolve hydroxyethyl cellulose in the remaining water and add it to the second mixture for mixing. Then add a water reducer and a defoamer for mixing. After forming, cure for 28 days to obtain a self-compacting machine-made sand concrete for the Yellow River flood plain climate.
[0041] The water reducing agent in this embodiment is selected from polycarboxylate water reducing agent.
[0042] The stimulator in this embodiment is selected from sodium sulfate.
[0043] The particle size of the stones in this embodiment is 5-10 mm.
[0044] The diameter of the polypropylene fiber in this embodiment is 30-50 μm and the length is 10-15 cm.
[0045] The defoaming agent in this embodiment is selected from silicone defoaming agent.
[0046] Embodiment 2-4 Example 2 The difference between this embodiment and embodiment 1 is that when preparing self-compacting machine-made sand concrete for the Yellow River flood plain climate, the total weight of the polypropylene fiber and the hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules is 320 parts, and the weight ratio of the polypropylene fiber and the hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules is 1:0.8.
[0047] Example 3 The difference between this embodiment and embodiment 1 is that when preparing self-compacting machine-made sand concrete for the Yellow River flood plain climate, the total weight of the polypropylene fiber and the hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules is 320 parts, and the weight ratio of the polypropylene fiber and the hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules is 1:1.1.
[0048] Example 4 The difference between this embodiment and embodiment 1 is that, when preparing self-compacting machine-made sand concrete for the Yellow River flood plain climate, the total weight of the polypropylene fiber and the hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules is 320 parts, and the weight ratio of the polypropylene fiber and the hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules is 1:1.2.
[0049] Comparative Examples 1-4 Comparative Example 1 The difference between this comparative example and Example 1 is that no polypropylene fiber is added when preparing the self-compacting machine-made sand concrete for the Yellow River flood plain climate.
[0050] Comparative Example 2 The difference between this comparative example and Example 1 is that no microcapsules of hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine are added when preparing the self-compacting machine-made sand concrete for the Yellow River flood plain climate.
[0051] Comparative Example 3 The difference between this comparative example and Example 1 is that when preparing the self-compacting machine-made sand concrete for the Yellow River flood plain climate, the hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules and polypropylene fibers are not added.
[0052] Comparative Example 4 The difference between this comparative example and Example 1 is that when preparing the self-compacting machine-made sand concrete for the Yellow River flood plain climate, an equal amount of acetylated distarch phosphate is used to replace the hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules.
[0053] Experimental testing: Compressive strength: The compressive strength is tested with reference to GB / T500812019. The test sample is 100mm×100mm×100mm.
[0054] The shrinkage rate of concrete is tested according to the non-contact method in GB / T50082-2009 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete".
[0055] The experimental test results of Examples 1-4 and Comparative Examples 1-3 are shown in Table 1.
[0056] Table 1 - Experimental test results of Examples 1-4 and Comparative Examples 1-3 Result analysis: The difference between Example 2-4 and Example 1 is that when preparing self-compacting machine-made sand concrete for the Yellow River flood plain climate, the weight ratio of polypropylene fiber and hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules is different. Combined with the experimental test results in Table 1, it can be seen that when the weight ratio of polypropylene fiber and hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules is 3.3:1, the compressive strength and shrinkage resistance of the self-compacting machine-made sand concrete for the Yellow River flood plain climate are better.
[0057] The difference between Comparative Example 1 and Example 1 is that when preparing the self-compacting machine-made sand concrete for the Yellow River flood plain climate, no polypropylene fiber is added. The difference between Comparative Example 2 and Example 1 is that when preparing the self-compacting machine-made sand concrete for the Yellow River flood plain climate, no hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules are added. The difference between Comparative Example 3 and Example 1 is that when preparing the self-compacting machine-made sand concrete for the Yellow River flood plain climate, no hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules and polypropylene fibers are added. Combined with the experimental test results of Table 1, it can be seen that when preparing the self-compacting machine-made sand concrete for the Yellow River flood plain climate, the self-compacting machine-made sand concrete for the Yellow River flood plain climate obtained by compounding the hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules and polypropylene fibers is better in compressive strength and shrinkage resistance. The reason may be that the compounding of polypropylene fibers and hydrophobic microcapsules produces a common effect. Polypropylene fiber effectively hinders the expansion of cracks by forming a physical network in the concrete matrix, enhancing the toughness and crack resistance of concrete. Hydrophobic microcapsules reduce drying stress by adjusting the internal moisture balance, and the components released after rupture help the self-healing of cracks, thereby jointly improving the shrinkage resistance of concrete. The addition of hydrophobic microcapsules improves the microstructure of concrete, which may enhance the density of concrete by filling pores and microcracks, reduce water evaporation channels, and further improve the overall stability of concrete in synergy with the action of polypropylene fibers. The distribution of fibers and microcapsules in concrete can effectively disperse stress and reduce local stress concentration. At the same time, the slow release mechanism of microcapsules can continuously replenish water and relieve the internal stress caused by drying, thereby reducing the generation of cracks. In summary, the compound use of polypropylene fiber and hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules improves the compressive strength and shrinkage resistance of self-compacting machine-made sand concrete for the Yellow River flood plain climate by improving the microstructure of concrete, enhancing internal moisture management, and providing stress dispersion and self-healing mechanisms.
[0058] The difference between Comparative Example 4 and Example 1 is that, when preparing self-compacting machine-made sand concrete for the Yellow River flood plain climate, an equal amount of acetylated distarch phosphate is used to replace the microcapsules of hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine. It can be seen from the experimental test results in combination with Table 1 that when the microcapsules of hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine are replaced with an equal amount of acetylated distarch phosphate, the anti-shrinkage effect of concrete is reduced, and the reason may be that in Example 1, acetylated distarch phosphate is wrapped in microcapsules, and can be released in time according to the changes in the internal environment of concrete (such as the formation of microcracks caused by drying), so as to more accurately regulate local moisture balance and promote self-healing process. In Comparative Example 4, acetylated distarch phosphate is directly mixed into concrete, loses the slow-release mechanism, and cannot be effectively released when needed, which affects its contribution to the internal moisture regulation of concrete and the self-healing ability of cracks. As the shell of microcapsules, hydrophobic porous ceramsite can not only protect the internal components, but also form tiny hydrophobic areas in concrete, which helps to reduce water penetration and improve the impermeability of concrete. The direct use of acetylated distarch phosphate loses this hydrophobic protective layer, which reduces the ability of concrete to manage moisture and makes it more susceptible to the adverse effects of dry-wet cycles. Microcapsule technology ensures the uniform distribution of acetylated distarch phosphate in concrete. Each microcapsule plays an independent role inside the concrete. Even if it breaks in a local area, it can effectively cover the surrounding area and achieve efficient utilization. Acetylated distarch phosphate added directly may be unevenly distributed during the concrete mixing process. The concentration may be too high in some areas and too low in others, affecting its overall performance. In summary, although acetylated distarch phosphate itself has a certain hydrophilicity and potential self-healing effect, the microcapsule structure formed by its encapsulation in hydrophobic porous ceramsite is crucial to achieve effective moisture regulation, crack self-healing and improve the shrinkage resistance of concrete. Direct replacement with non-microencapsulated acetylated distarch phosphate lacks the above advantages, resulting in reduced anti-shrinkage properties.
[0059] Embodiment 5-6 Example 5 The difference between this embodiment and embodiment 1 is that when preparing the self-compacting machine-made sand concrete for the Yellow River flood plain climate, the weight proportions of some components are changed. The differences are shown in Table 2.
[0060] Table 2 - Differences between Example 5-6 and Example 1 The experimental test results of Examples 5-6 are shown in Table 3.
[0061] Table 3 - Experimental test results of Examples 5-6 Result analysis: The difference between Example 5-6 and Example 1 is that when preparing the self-compacting machine-made sand concrete for the Yellow River Flood Plain climate, the weight proportions of some components are different. Combined with the experimental test results in Table 3, it can be seen that the comprehensive performance of the self-compacting machine-made sand concrete for the Yellow River Flood Plain climate prepared by Example 5 is better.
[0062] Embodiment 7-11 Example 7 The difference between Example 7-11 and Example 5 is that when preparing self-compacting machine-made sand concrete for the climate of the Yellow River Flood Plain, on the premise that the weight ratio of polypropylene fiber and hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules is 1:1, the total weight ratio of polypropylene fiber and hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules in the self-compacting machine-made sand concrete for the climate of the Yellow River Flood Plain is changed, and the optimal weight ratio is selected.
[0063] In Example 5, the total weight of the polypropylene fiber and the hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules is 320 parts, and the total weight of the self-compacting machine-made sand concrete for the Yellow River flood plain climate is 3616 parts.
[0064] Therefore, it is not difficult to conclude that in Example 5, the proportion of polypropylene fiber (called variable 1) and hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules (called variable 2) in the self-compacting machine-made sand concrete for the Yellow River Flood Plain climate (called the matrix) is 8.58%.
[0065] The differences between Examples 7-11 and Example 5 are shown in Table 4.
[0066] Proportion = (variable 1 + variable 2) / total weight of matrix * 100%.
[0067] Table 4 - Differences between Examples 7-11 and Example 5 The experimental test results of Examples 7-11 are shown in Table 5.
[0068] Table 5 - Experimental test results of Examples 7-11 Result analysis: The difference between Example 7-11 and Example 5 is that when preparing the self-compacting machine-made sand concrete for the Yellow River flood plain climate, the total weight of the polypropylene fiber and the hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules in the self-compacting machine-made sand concrete for the Yellow River flood plain climate is different. Combined with the experimental test results of Table 5, it can be seen that when the total weight of the polypropylene fiber and the hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules in the self-compacting machine-made sand concrete for the Yellow River flood plain climate accounts for 7.83-10.82%, the self-compacting machine-made sand concrete for the Yellow River flood plain climate has better comprehensive performance, and when the total weight of the polypropylene fiber and the hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules in the self-compacting machine-made sand concrete for the Yellow River flood plain climate accounts for 10.58%, the self-compacting machine-made sand concrete for the Yellow River flood plain climate has the best comprehensive performance. When the proportion is too high or too low, the comprehensive performance is reduced.
[0069] Examples 12-13 Example 12 The difference between this embodiment and embodiment 10 is that when preparing self-compacting machine-made sand concrete for the Yellow River flood plain climate, the preparation parameters of the hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules used are different, and the polypropylene fiber in this embodiment is prepared by Preparation Example 2.
[0070] Example 13 The difference between this embodiment and embodiment 10 is that when preparing self-compacting machine-made sand concrete for the Yellow River flood plain climate, the preparation parameters of the hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules used are different, and the polypropylene fiber in this embodiment is prepared by Preparation Example 3.
[0071] The experimental test results of Examples 12-13 are shown in Table 6.
[0072] Table 6 - Experimental test results of Examples 12-13 Result analysis: The difference between Example 12-13 and Example 10 is that the preparation parameters of the hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules used in the preparation of the self-compacting machine-made sand concrete for the Yellow River flood plain climate are different. Combined with the experimental test results in Table 6, it can be seen that the self-compacting machine-made sand concrete for the Yellow River flood plain climate prepared by Example 12 has better comprehensive performance.
[0073] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A self-compacting machine-made sand concrete for the Yellow River flood plain climate, characterized in that: The concrete comprises the following raw materials by weight: 400-450 parts of cement; Silica fume 85-105 parts; Mineral powder 200-220 parts; Fly ash 170-195 parts; 900-1050 pieces of stone; 850-940 parts of machine-made sand; Steel fiber 283-295 parts; Polypropylene fiber 100-200 parts; Water reducing agent 18.5-21.5 parts; Hydroxyethyl cellulose 0.4-0.6 parts; Defoaming agent 0.5-1 part; 1319 parts of stimulant; 130-140 parts of water; Silane coupling agent KH-792 5-10 parts; 100-200 parts of hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules; The preparation method of the hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules comprises the following steps: A1. Add a hydrochloric acid solution with a concentration of (6-10) mol / L to the porous ceramsite, heat and stir for 3-5 hours in a water bath, centrifuge to separate the solid matter, and wash and grind the solid matter to obtain the porous ceramsite after hydrochloric acid etching; A2, the porous ceramsite etched with hydrochloric acid obtained in step A1, acetylated distarch phosphate and water are mixed, and ultrasonically dispersed for 50-70 minutes under ice bath conditions to obtain a suspension, and the obtained suspension is vacuum dried. When the vacuum degree in the dryer reaches -0.1 MPa during vacuum drying, it is maintained for 20-30 minutes, and then restored to 0.1 MPa; A3. After vacuum drying, centrifuge to separate the solid phase, wash the solid phase, vacuum dry for 24-30 hours, grind into powder, and obtain porous ceramsite loaded with acetylated distarch phosphate after hydrochloric acid etching; A4, tris(hydroxymethyl)aminomethane, dopamine hydrochloride, the porous ceramsite loaded with acetylated distarch phosphate obtained after hydrochloric acid etching in step A3, and water in a weight ratio of (2-3): (1-1.5): 1: (180-200), and adjusting the pH to 8.0-9.0, ultrasonically dispersing for 15-20 minutes, stirring for 6-8 hours, centrifugally washing, and drying to obtain a porous ceramsite-acetylated distarch phosphate-polydopamine composite; A5, placing the porous ceramsite-acetylated distarch phosphate-polydopamine complex obtained in step A4 into a solution of hexadecyltrimethoxysilane and ethanol, soaking for 3-5 hours, and drying to obtain the hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules; The weight ratio of the porous ceramsite to the hydrochloric acid solution in step A1 is (10-12): (100-120); The weight ratio of the acetylated distarch phosphate and water in step A2 to the porous ceramsite in step A1 is (15-20): (60-80): 1; The weight ratio of hexadecyltrimethoxysilane, ethanol and the porous ceramsite-acetylated distarch phosphate-polydopamine complex in step A4 is (0.8-1.2):20:
10.
2. The self-compacting machine-made sand concrete for the Yellow River flood plain climate according to claim 1, characterized in that: The weight ratio of the polypropylene fiber to the hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsule is 1:(0.8-1.2).
3. The self-compacting machine-made sand concrete for the Yellow River flood plain climate according to claim 2, characterized in that: The weight ratio of the polypropylene fiber to the hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules is 1:
1.
4. The self-compacting machine-made sand concrete for the Yellow River flood plain climate according to claim 1, characterized in that: The total weight of the polypropylene fiber and the hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules accounts for 8-11% of the total weight of the self-compacting machine-made sand concrete for the Yellow River flood plain climate.
5. The self-compacting machine-made sand concrete for the Yellow River flood plain climate according to claim 4, characterized in that: The total weight of the polypropylene fiber and the hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules accounts for 10.5% of the total weight of the self-compacting machine-made sand concrete for the Yellow River flood plain climate.
6. The self-compacting machine-made sand concrete for the Yellow River flood plain climate according to claim 1, characterized in that: The water reducer is selected from polycarboxylate water reducer.
7. The self-compacting machine-made sand concrete for the Yellow River flood plain climate according to claim 1, characterized in that: The activator is selected from sodium sulfate.
8. The self-compacting machine-made sand concrete for the Yellow River flood plain climate according to claim 1, characterized in that: The particle size of the stone is 5-10mm.
9. The self-compacting machine-made sand concrete for the Yellow River flood plain climate according to claim 1, characterized in that: The polypropylene fiber has a diameter of 30-50 μm and a length of 10-15 cm.
10. A method for preparing the self-compacting machine-made sand concrete for the Yellow River flood plain climate according to any one of claims 1 to 9, characterized in that: The preparation method comprises the following steps: S1, dissolving silane coupling agent KH-792 in ethanol, adding polypropylene fiber and steel fiber for impregnation treatment, and drying to obtain modified fiber; S2, dividing the water into two equal parts, mixing one part of the water with cement, mineral powder, fly ash, activator, silica fume, machine-made sand, gravel, and modified fiber to prepare a first mixed material; S2, adding hydrophobic porous ceramsite-acetylated distarch phosphate-polydopamine microcapsules to the mixture and mixing and stirring to obtain a second mixture; S4, dissolving hydroxyethyl cellulose in the remaining water, adding the mixture to the second mixture and mixing, then adding a water reducer and a defoamer and mixing, and curing after forming to obtain the self-compacting machine-made sand concrete for the Yellow River flood plain climate.